Post-hatching behaviour of Light-bellied Brent Geese Branta bernicla hrota - Bregnballe, Thomas; Madsen, Jesper (Wildfowl, 1990)
Time budget, spacing and antipredator behaviour of Light-bellied Brents were studied on an island in southeast Svalbard during the first three weeks of post-hatching. Male parents spent equal amounts of time on feeding and vigilance (33%), whereas females grazed more (46%) than they were vigilant (16%). For all geese more resting took place at night than around midday. Vigilance in the head up posture was less frequent during night than during day. At the time of loss of remiges non-breeder feeding activity declined from 60% to 35%; they flocked and began to follow families, even though attacked by male parents. When parents began moulting their remiges they became more gregarious and more tolerant towards non-breeders. Short distances between family members and between families, a high frequency of alert behaviour and effective antipredator responses including collective protection are suggested to account for the survival of all 90 goslings in the study area. We discuss how changes in the risk of predation of goslings and adults influence the extent of flocking.